2012
DOI: 10.1177/0003319712436577
|View full text |Cite
|
Sign up to set email alerts
|

Value of Albumin–Globulin Ratio as a Predictor of All-Cause Mortality After Non-ST Elevation Myocardial Infarction

Abstract: Low albumin and the albumin-globulin ratio (AGR) were associated with vascular adverse events. Our study explores the AGR as a predictor of mortality after non-ST-segment elevation myocardial infarction (NSTEMI). In an observational study of 570 NSTEMI patients admitted to a tertiary center between 2004 and 2006, patients were stratified into equal tertiles according to AGR. The primary outcome was 4-year all-cause mortality. The 4-year mortality rates in the first, second, and third AGR tertiles were 88 (47%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 39 publications
(48 reference statements)
4
11
0
Order By: Relevance
“…Hypoalbuminemia, previously considered a mortality predictor following myocardial infarction [44], has also been reported to be predictive of 1 year mortality among heart failure patients [45]. Classically linked to frailty, in our sample, albumin levels appeared to be related to CI.…”
Section: Discussionsupporting
confidence: 58%
“…Hypoalbuminemia, previously considered a mortality predictor following myocardial infarction [44], has also been reported to be predictive of 1 year mortality among heart failure patients [45]. Classically linked to frailty, in our sample, albumin levels appeared to be related to CI.…”
Section: Discussionsupporting
confidence: 58%
“…In addition to the suggested genetic correlations in Europeans (type 2 diabetes and BMI; triglycerides, blood sugar, and hemoglobin A1c; coronary artery disease and BMI; and high-density-lipoprotein cholesterol and triglycerides) 15 , we empirically corroborated novel genetic correlations that have been implicated in Mendelian randomization analyses (e.g., type 2 diabetes and alanine aminotransferase 31 ; atrial fibrillation and height 32 ; asthma and eosinophil count 9 ; and colorectal cancer and height 33 ) and epidemiological studies (e.g., ischemic stroke and uric acid 34 ; myocardial infarction and albumin/globulin ratio 35 ; peripheral artery disease and total Tables 1 and 2. bilirubin 36 ; and urolithiasis and blood pressure 37 ) (Supplementary Table 8). Thus, we further investigated causal relationships between the significant pairs of quantitative traits and diseases by using a Mendelian randomization approach (Methods).…”
Section: And Supplementarysupporting
confidence: 67%
“…These findings are consistent with the previous studies [19,25]. Beamer et al found diabetes was more common in patients with lower AGR and presumed low AGR as a marker of severity of the pathophysiological changes related to chronic disease, such as diabetes [25].…”
Section: Discussionsupporting
confidence: 93%
“…The association of AGR and mortality had been reported by previous studies on varied populations, including non-ST elevation myocardial infarction [19], colorectal cancer [20,21], hepatocellular carcinoma [22], and early-stage non-small cell lung cancer [23]. Suh et al reported low AGR was a risk factor for cancer incidence and mortality, both in the short-and long terms, in 26,974 healthy patients [24].…”
Section: Discussionmentioning
confidence: 75%